COMPLEMENTARY AND ALTERNATIVE MEDICINE USERS IN SERBIA HEALTH SELF-EVALUATION: CROSS-SECTIONAL NATIONAL STUDY - Luketina-Šunjka, Marina; Rančić, Nemanja; Mihailović, Nataša; Radević, Svetlana; Dragović, Saša; Jakovljević, Mihajlo (Acta medicae Medianae, 2021)
The aim of the research was to examine the influence of the respondents' health status on the use of complementary and alternative medicine methods. This was a population-based, cross-sectional study. The sample consisted of 550 interviewed persons, from the third National health survey of the residents of Serbia in 2013, who had used complementary and alternative medicine (CAM) services in the preceding 12 months. Just over 2/3 of CAM users have chronic health disorders (p
Keywords: Health self-assessment; Health status; Complementary and alternative medicine; Chronic diseases